Atmospheric CO2 Variations in Two Contrasting Environmental Sites Over India. Issue 7 (January 2014) - Sharma, Neerja; Dadhwal, V.K.; Kant, Y.; Mahesh, P.; Mallikarjun, K.; Gadavi, Harish; Sharma, Anand; Ali, M.M.
We analyzed the influence of environmental parameters on the temporal variation of atmospheric carbon dioxide (CO2 ) mixing ratios in two environmentally contrasting Indian sites, Dehradun (30.1°N, 77.4°E, humid subtropical station) and Gadanki (13.5°N, 79.18°E, dry tropical station), from October 2010 to September 2011. The annual range of mixing ratios is low in Gadanki as compared to those of Dehradun because of relatively less monthly variation in temperature and relative humidity (RH) at Gadanki. At both the stations, the minimum mixing ratios are present during the high ecosystem productivity seasons in the afternoon hours. The maximum values are in the early morning hours. However, low wind speed conditions control the unexpected afternoon high mixing ratios in Gadanki during the pre-monsoon season. The early morning maximum is high during monsoon and post-monsoon seasons in Dehradun and Gadanki, respectively, whereas morning inflexion occurred earlier in Gadanki compared with Dehradun. The effect of cloudiness on the CO2 uptake depends on the canopy cover.